A Primer of Neoclassical (Traditional) and Behavioral Economic Principles for Organ Transplantation: Part 2. Issue 11 (November 2015) - Schnier, Kurt E.; Turgeon, Nicole; Kaplan, Bruce
Abstract : Schnier and colleagues continue their primer on the application of behavioral economics to real world issues in transplantation. Framing effects, discounting, marginal rate of substitution, and regarding preferences all have profound effects on patient, physician, and institutional choices and behaviors.